Contemporary Issues in Family Law and Mental Health. - Brock, Michael G. (American series in behavioral science and law ; 1112 Contemporary issues in family law and mental health, 2008)
Contemporary Issues in Family Law and Mental Health is an original and practical discussion of cutting-edge issues in family relations and the law. Through the prism of family law, and custody disputes in particular, it discusses the basic principles that underlie the proper use of mental health evidence in court and it sets out the proper use of mental health evidence in litigation. The first and most important principal is that forensic mental health practice and procedures must track the legal process, not the other way around. The goal of mental health treatment is fundamentally different.